The Role of Notaries in the Cooperation Agreement Between PT. Perhotelan Resty Menara and the Youth and Sports Office of Pekanbaru City - Sari, Riana (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study aims to determine and analyze the role of notaries in the implementation of the Cooperation Agreement between PT. Perhotelan Resty Menara and the Youth and Sports Office of Pekanbaru City, as well as to determine and analyze the Implementation of the Cooperation Agreement in accordance with the Agreement that has been made in the Cooperation Agreement between PT. Perhotelan Resty Menara and the Youth and Sports Office of Pekanbaru City. The research approach method used in this thesis is the sociological juridical legal research method. The specifications of this study use descriptive analysis. Data collection using interview techniques and document studies or library materials. The practical benefits of this study are expected to be used to formulate Cooperation arrangements between the Regional Government and the Private Sector in implementing cooperation in the context of developing Contract Law in Indonesia. The results of the study indicate that the role of notaries in the implementation of the Cooperation Agreement between PT. Resty Menara Hotel with the Pekanbaru City Youth and Sports Service has an important role in creating legal certainty in every legal relationship. Given the importance of notary involvement in making cooperation agreements between private companies and the government, certain requirements are required in making agreements so that the agreement remains in accordance with applicable laws and regulations. This is done by both parties because they realize that in addition to the main task of a notary is to create or record events authentically, the parties also realize that the involvement of a notary's role is more than that regulated in the law, especially as a mediator in differences of opinion on something in a legal relationship.